The talking button / Muhammad Alfateh Mohd Nuhairi and Abdul Karim Endot @Azlan - Mohd Nuhairi, Muhammad Alfateh; Endot @Azlan, Abdul Karim (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Children with speech difficulties struggle to express themselves, and caregivers lack clear insights into their behavior patterns. Develop a communication aid promoting clear need expression and introduce data collection for behavior analysis, ultimately enhancing teacher/caretaker understanding. This "Talking Button" prioritizes data collection due to micro bit limitations. Button presses (e.g., "toilet" and "hungry") are tracked, providing real-time data through the Serial Monitor (optional: explore advanced storage). Button presses allow essential communication. Data offers insights into student behavior, enabling personalized care plans and addressing individual needs. The Talking Button has the potential for commercialization as a low-cost, adaptable communication and data-collection tool for children with speech difficulties. The open-source nature of the micro-bit platform allows for further development and customization.